Emmonsiellopsis, a new genus related to the thermally dimorphic fungi of the family Ajellomycetaceae. Issue 8 (19th June 2015) - Marin‐Felix, Y.; Stchigel, A. M.; Cano‐Lira, J. F.; Sanchis, M.; Mayayo, E.; Guarro, J.
Summary: Two interesting fungi were isolated from fluvial sediments collected in the North of Spain. They were morphologically related to the thermally dimorphic fungi of the family Ajellomycetaceae, but the analysis of the internal transcribed spacer region of the rDNA, and the domains D1 and D2 of the 28S rRNA gene sequences confirmed that they were different from all the species described in that family. They were accommodated in the new genus Emmonsiellopsis as E. coralliformis sp. nov. and E. terrestris sp. nov. The two species are distinguished mainly by the maximum temper‐ature of growth (up to 33 °C for E. coralliformis and to 42 °C for E. terrestris ), the dendritic mycelium of E. coralliformis and the conidial ornamentation (verrucose in E. coralliformis and spinulose in E. terrestris ). In addition, the phylogenetic data demonstrated that Ajellomyces griseus also represents a new genus within the Ajellomycetaceae, namely Helicocarpus . This new genus is easily distinguished by the lack of asexual morph, the production of brownish gymnothecial ascomata and oblate to lenticular, sparingly pitted ascospores. The proposal of both new genera was confirmed by the analysis of actin gene sequences.